Opioid Overdose and Naloxone Dosing at Insite Supervised Injection Facility in British Columbia: A Retrospective Cohort Study. Issue 4 (1st December 2022) - Cho, Raymond; Purssell, Roy; Joe, Ronald; Wang, Yueqiao Elle; O'Sullivan, Fiona; Lin, Kathleen; Rowe, Adrianna; Moe, Jessica
ABSTRACT: Objectives: We aimed to understand trends in opioid overdoses, naloxone dosing, and overdose reversal from 2014 to 2017 at Insite, a community-supervised consumption site in Vancouver, British Columbia. Methods: We performed a retrospective cohort study of patients who overdosed on opioids at Insite. We evaluated yearly trends in total overdoses, naloxone doses administered, and proportions of patients reversed (based on our definitions of "probable" and "confirmed" reversal), with particular attention to trends before and after the emergence of illicit fentanyl in 2015. Results: There was an increase in total overdoses at Insite from 2014–2015 (n=586) to 2016–2017 (n=2033). Overdose reversal data were limited by a large proportion of patients for whom there was not enough information to adjudicate whether reversal occurred, and therefore were marked "unspecified" [n=1537/2619 (58.7%)]. Within these limitations, fewer patients were reversed after 2015 (44.1% in 2016, 29.7% in 2017) than before (47.8% in 2014, 55.1% in 2015) (χ 2 =73.1, P <0.001). Despite this, naloxone doses remained unchanged between 2014–2015 and 2016–2017 median: 0.4 mg [interquartile range (IQR): 0.4–0.8 mg] for both, P =0.21. Insite staff administered higher doses to patients not successfully reversed [median: 0.8 mg (IQR: 0.4–0.8 mg)] compared with those reversed [median: 0.4 mg (IQR: 0.4–0.8 mg)] ( P =0.021), and to patients offered transfer to hospital [median: 0.8 mg (IQR: 0.4–0.8 mg)] compared with those discharged home [median: 0.4 mg (IQR: 0.4–0.8 mg)] (Kruskal-Wallis H =288.7, P <0.001). Conclusion: Overdose numbers at Insite increased and fewer patients were successfully reversed following the emergence of illicit fentanyl in 2015, but naloxone doses remained unchanged, suggesting that traditional naloxone dosing does not optimally reverse overdoses caused by fentanyl. Our study supports an alternative approach to naloxone dosing in patients with suspected ultrapotent opioid toxicity and in communities with high fentanyl prevalence. Abstract : Objectifs: Nous avons cherché à comprendre les tendances en matière de surdoses d'opioïdes, de dosage de naloxone et de renversement des effets de surdosage de 2014 à 2017 à Insite, un site communautaire de consommation supervisée à Vancouver, en Colombie-Britannique (C.-B.). Méthodes: Nous avons réalisé une étude de cohorte rétrospective des patients ayant fait une surdose d'opioïdes à Insite. Nous avons évalué les tendances annuelles du total des surdoses, des doses de naloxone administrées et des proportions de patients qui ont renversé les effets de surdosage (selon nos définitions de "probable" et "confirmée"), en accordant une attention particulière aux tendances avant et après l'émergence du fentanyl illicite en 2015. Résultats: Il y a eu une augmentation du nombre total de surdoses à Insite entre 2014-2015 (n=586) et 2016-2017 (n=2033). Les données sur le renversement des effets de surdosage étaient limitées par une grande proportion de patients pour lesquels il n'y avait pas assez d'informations pour juger si le renversement des effets de surdosage avait eu lieu, et ont donc été marquées " non spécifié " (n=1537/2619 [58, 7%]). Dans le cadre de ces limitations, moins de patients ont été renversé après 2015 (44, 1% en 2016, 29, 7% en 2017) qu'avant (47, 8% en 2014, 55, 1% en 2015) (χ2=73, 1, P <0, 001). Malgré cela, les doses de naloxone sont restées inchangées entre 2014-2015 et 2016-2017 (médiane de 0, 4 mg [IQR 0, 4-0, 8 mg] pour les deux, P =0, 21). Le personnel d'Insite a administré des doses plus élevées aux patients dont le renversement n'a pas réussi (médiane de 0, 8 mg [IQR 0, 4-0, 8 mg]) par rapport à ceux dont le renversement a réussi (médiane de 0, 4 mg [IQR 0, 4-0, 8 mg] ( P =0. 021), et aux patients à qui l'on a proposé un transfert à l'hôpital (médiane 0, 8 mg [IQR 0, 4-0, 8 mg]) par rapport à ceux qui ont été renvoyés chez eux (médiane 0, 4 mg [IQR 0, 4-0, 8 mg]) (Kruskal-Wallis H=288, 7, P <0, 001). Conclusion: Le nombre de surdoses à Insite a augmenté et moins de patients ont renversé les effets de surdosage avec succès après l'émergence du fentanyl illicite en 2015, mais les doses de naloxone sont restées inchangées, ce qui suggère que le dosage traditionnel de la naloxone ne renverse pas de manière optimale les surdoses causées par le fentanyl. Notre étude soutient une approche alternative au dosage de la naloxone chez les patients soupçonnés de toxicité aux opioïdes ultrapuissants et dans les communautés à forte prévalence de fentanyl.